Meta-analyses in management: What can we learn from clinical research? - Antonio Sartal; Miguel González-Loureiro; Xosé H. Vázquez (BRQ Business Research Quarterly, 2021)
We analyze the weaknesses of meta-analyses (MAs) in management research using as benchmark a scientific field where this technique shows a longer tradition: clinical research. We suggest four areas in which management research MA practices should improve: (1) availability of information and replicability of primary research, (2) correct application of statistical support, (3) execution of heterogeneity analyses, and (4) standardization of result reporting. Using a representative MA on an operations management topic, we identify qualitatively the aspects to be improved at each stage. We show the different results that could have been achieved by following standard procedures in clinical research, incorporating different "good practices" from this research field. Overall, these recommendations aim at improving the transparency and replicability of MAs, which can not only facilitate the accumulation of scientific knowledge but also intensify the dialogue between academia and practitioners.
Keywords: C01; M11; M01; 650; Meta-analysis; "good practices"; transparency; replicability; management; clinical research